Respuesta :

The fundamental theorem of algebra says this cubic has three roots, so we could write it as

[tex]4x^3+32x^2+79x+60=4(x-a)(x-b)(x-c)[/tex]

We're told one of the roots is equal to the sum of the other two, so we could take [tex]c=a+b[/tex]:

[tex]4x^3+32x^2+79x+60=4(x-a)(x-b)(x-a-b)[/tex]

If we expand the right side, we get

[tex]4\bigg(x^3-2(a+b)x^2+(a^2+3ab+b^2)x-(a^2b+ab^2)\bigg)[/tex]

For two polynomial to be equal, the coefficients of terms of the same degree must match, so that

[tex]\begin{cases}4=4&(x^3)\\32=-8(a+b)&(x^2)\\79=4(a^2+3ab+b^2)&(x)\\60=-4(a^2b+ab^2)&\text{(constant)}\end{cases}[/tex]

Now we can find [tex]a,b,c[/tex].

[tex]32=-8(a+b)=-8c\implies c=-4[/tex]

This tells us that [tex]x+4[/tex] is a factor, so dividing the original cubic by this returns a remainder of 0.

[tex]\dfrac{4x^3+32x^2+79x+60}{x+4}=4x^2+16x+15=4\left(x+\dfrac32\right)\left(x+\dfrac52\right)[/tex]

which further tells us that [tex]a=-\dfrac32[/tex] and [tex]b=-\dfrac52[/tex].

ACCESS MORE